2010
DOI: 10.1016/j.jad.2009.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and migraine comorbidity among pregnant Peruvian women

Abstract: Background Migraine and depression are known to be comorbid conditions in non-pregnant women and men. However, the migraine-depression comorbidity among pregnant women, particularly women in developing countries has not been evaluated. Therefore, we evaluated the migraine-depressive symptom relationship in a large cohort of pregnant Peruvian women. Methods Women who delivered singleton infants (N=2,293) at the Instituto Nacional Materno Perinatal, Lima, Peru were interviewed during the postpartum hospital st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 38 publications
(49 reference statements)
3
24
0
Order By: Relevance
“…In the present study, the high prevalence of mood disorders and psychosocial stressors in Peru (e.g., antenatal depression, childhood abuse, and intimate partner violence) may account for the high prevalence of suicidal ideation (Cripe et al 2010; Farber et al 1996; Gavin et al 2011; Lindahl et al 2005; Perales et al 2009; WHO 2005). Of note, Devries et al (Devries et al 2011) found that intimate partner violence was a consistent risk factor for suicide behaviors even after adjusting for probable common mental disorders.…”
Section: Discussionmentioning
confidence: 75%
“…In the present study, the high prevalence of mood disorders and psychosocial stressors in Peru (e.g., antenatal depression, childhood abuse, and intimate partner violence) may account for the high prevalence of suicidal ideation (Cripe et al 2010; Farber et al 1996; Gavin et al 2011; Lindahl et al 2005; Perales et al 2009; WHO 2005). Of note, Devries et al (Devries et al 2011) found that intimate partner violence was a consistent risk factor for suicide behaviors even after adjusting for probable common mental disorders.…”
Section: Discussionmentioning
confidence: 75%
“…The prevalence of antepartum depression ranges from 10% to 41% in LMICs (Organization, 2008). In a recent study, 41% of Peruvian women reported moderate to severe depressive symptoms during their entire pregnancy (Cripe et al, 2010). Depressive disorders during pregnancy are associated with adverse obstetric (de Paz et al, 2011, Qiu et al, 2007, Sanchez et al, 2013) and neonatal outcomes (Chung et al, 2001, Lou et al, 1994, Zuckerman et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Given the high prevalence of depressive symptoms during pregnancy in Peru (Cripe et al, 2010) and the lack of studies evaluating the comparability of the two scales during pregnancy, we conducted the present study to compare the psychometric properties of PHQ-9 and EPDS among pregnant Peruvian women. Specifically, as an initial step towards developing clinical intervention studies to mitigate the burden of depressive disorders among pregnant women in Peru, we sought to evaluate the construct validity of the two scales by evaluating their factor structures.…”
Section: Introductionmentioning
confidence: 99%
“…The co-occurrence of migraine and mood disorders has been well documented in non-pregnant populations (Breslau et al, 1994; Breslau et al, 2003; Fuller-Thomson et al, 2013; Gelaye et al, 2013; Jette et al, 2008; Kalaydjian and Merikangas, 2008; McWilliams et al, 2004; Merikangas et al, 1990; Nguyen and Low, 2013; Patel et al, 2004; Saunders et al, 2014; Swartz et al, 2000; Zwart et al, 2003). Recent evidence suggests that migraine and mood disorders may be common among pregnant women (Cripe et al, 2010; Williams et al, 2010). In a study of 2,293 pregnant women, 55.1% of migraineurs reported moderate to severe depressive symptoms during pregnancy compared to 36.7% of pregnant non-migraineurs (Cripe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that migraine and mood disorders may be common among pregnant women (Cripe et al, 2010; Williams et al, 2010). In a study of 2,293 pregnant women, 55.1% of migraineurs reported moderate to severe depressive symptoms during pregnancy compared to 36.7% of pregnant non-migraineurs (Cripe et al, 2010). Furthermore, migraineurs score higher on the Perceived Stress Scale (PSS) than non-migraineurs during the first trimester of pregnancy (mean ± SD: 4.2 ± 2.4 vs. 3.7 ± 2.3; p-value: 0.008) (Williams et al, 2010).…”
Section: Introductionmentioning
confidence: 99%